Digitalized co-production of emergency response: ICT-enabled dispatch and coordination of volunteers at the emergency site - Sofie Pilemalm; Anna Follin; Erik Prytz (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – Volunteers play an increasingly important role in emergency response logistics. However, to make most use of their capabilities, they need to be dispatched to the emergency site in an effective manner and coordinated on-site. The purpose of this study is to present a requirements specification and initial design proposal for ICT-enabled dispatch of volunteers as first responders as part of emergency response digitalized co-production initiatives. Design/methodology/approach – The study uses a case study approach inspired by action research and the theoretical lens of digitalized co-production. It includes a variety of methods for data collection, including interviews with volunteers, document analysis and participation in workshops. Findings – The major themes identified are geofencing, dispatch coordination, dynamic resource allocation and communication and collaboration. First priority requirements include geofencing alert and positioning, a joint application programming interface, receipt of alert, receipt if arrival at incident site, withdrawal of resources, chat functionality and the ability to alert in descending order within the geofenced areas to avoid alarm fatigue. As to coordination and dynamic resource allocation, e.g. built-in alert restrictions, ability to pre-select profiles and to dispatch based on competence/training, capacity and equipment would enable a more optimized response. Originality/value – While previous research on digital volunteerism mainly embraces spontaneous volunteers and social media, this study addresses long-time collaboration with professional response organizations – digitalized co-production – with a focus on the dispatch, coordination and task allocation of volunteers that are central to their integration with emergency response logistics.